2020
DOI: 10.1369/0022155420950841
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Role of E-Cadherin, β-Catenin, and Vimentin in Human Papillomavirus–Positive and Human Papillomavirus–Negative Oropharyngeal Squamous Cell Carcinoma

Abstract: Oropharyngeal squamous cell carcinoma (OPSCC) is subclassified by the World Health Organization into two different entities: human papillomavirus (HPV)-positive and HPV-negative tumors. HPV infection promotes the epithelial-to-mesenchymal transition (EMT) and transformation of keratinocyte stem cells into cancer stem cells. EMT is a crucial process in the carcinogenesis of epithelial-derived malignancies, and we aimed to study the role of its markers in OPSCC. This study consists of 202 consecutive OPSCC patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…E-cadherin is not only an epithelial marker during the occurrence of EMT, but also a regulator of YAP in controlling cancer cell proliferation, 55 while vimentin is a protein normally expressed in mesenchymal cells and serves as a canonical marker of EMT. 56 Notably, strong stromal vimentin expression was observed in 54% of human papillomavirus-positive OSCC clinical samples indicating the important role of vimentin in carcinogenesis. 56 The Bcl-2 family regulates apoptosis and holds great promise for cancer treatment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…E-cadherin is not only an epithelial marker during the occurrence of EMT, but also a regulator of YAP in controlling cancer cell proliferation, 55 while vimentin is a protein normally expressed in mesenchymal cells and serves as a canonical marker of EMT. 56 Notably, strong stromal vimentin expression was observed in 54% of human papillomavirus-positive OSCC clinical samples indicating the important role of vimentin in carcinogenesis. 56 The Bcl-2 family regulates apoptosis and holds great promise for cancer treatment.…”
Section: Discussionmentioning
confidence: 98%
“…The results of the present study showed that ATN decreased the levels of vimentin and YAP, accompanied by increased levels of E‐cadherin in SCC2095 cells. E‐cadherin is not only an epithelial marker during the occurrence of EMT, but also a regulator of YAP in controlling cancer cell proliferation, 55 while vimentin is a protein normally expressed in mesenchymal cells and serves as a canonical marker of EMT 56 . Notably, strong stromal vimentin expression was observed in 54% of human papillomavirus‐positive OSCC clinical samples indicating the important role of vimentin in carcinogenesis 56 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, cell membrane β-catenin expression was significantly associated with vimentin in HPV-associated oropharyngeal squamous cell carcinoma [63]. In an OSCCderived cell line Tca8113, treatment of exogenous TGFβ1 upregulated vimentin expression at both mRNA and protein levels.…”
Section: Vimentin In Late Stages Of Oral Cancermentioning
confidence: 96%
“…In addition, more and more experimental evidence links HPV infection to a pro‐oncogenic modulation of the Wnt/β‐catenin pathway [ 147 ]. For example, in oropharyngeal cancer, tumour cells infected with HPV expressed higher β‐catenin than HPV‐negative tumours [ 148 ]. Furthermore, the nuclear localization of β‐catenin was higher in HPV‐positive tumours than HPV‐negative control tumours [ 149 ], a characteristic also confirmed in tonsillar tumours [ 150 ].…”
Section: Papillomavirusesmentioning
confidence: 99%